Development of Learning Instruments Based on Experiential Learning Model of VIII SMP - Suanto, Elfis; Suhermi, Suhermi; Anita, Anita (Proceedings of the UR International Conference on Educational Sciences, 2018)
Limited learning instruments for innovative mathematics where students are used as learning centers in accordance with the demands of the 2013 curriculum. The innovative learning instruments referred to in this study are a learning tool in the form of learning implementation plans (RPP) supplemented by student worksheets (LKPD) based on experiential learning model. This model allegedly corresponds to the characteristics of teaching materials and characteristics of students. This study aims to produce learning tools based on experiential learning models on the material of cube and beam of class VIII SMP with a high level of validity and practicality. The form of this research was development research (R & D) using ADDIE development procedure; analyze, design, development, implementation, and evaluation. The object of this study is to develop a learning instrument based on experiential learning model on the material of cube and beam of class VIII SMP itself. After the RPP that is equipped with LKPD is declared valid by the expert, a trial is conducted on a larger class to examine the practical aspects. The subjects of the trial were 38 eighth grade students of SMP 21 Pekanbaru. The instrument used is a validation sheet consisting of 34 statement items and student response questionnaires to LKPD. The results of the study are that all validators have agreed on every aspect of assessment of the learning instrument, namely aspects of 1) format of learning instrument, 2) activities of the entire contents of learning instrument, 3) content of learning instrument, 4) pictures or graphics, and 5) language / text and 6 ) overall assessment of learning instrument. Then based on the results of data analysis about student response questionnaires to LKPD, it is obtained that 95.5% is with a very practical category. It can be concluded that innovative learning instruments in the form of RPP equipped with LKPD are based on experiential learning model on cube material and grade VIII SMP beam can be used in learning with a high level of validity and practicality.